2013
DOI: 10.1177/0038038513495604
|View full text |Cite
|
Sign up to set email alerts
|

The Marketization of Identity Politics

Abstract: Sociology has begun to question how new genetic sciences affect older ways of constructing and contesting social identity, including forms of identity politics that have brought women and minorities significant gains. This article presents US debates on genetics, identity politics, and race in order to theorize emergent transformations in light of the genomic revolution. Examining recent developments in the realms of pharmaceuticals and ancestry estimation, I argue that traditional forms of identity politics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…By ascribing racial or ethnic categories to the physical bodies of individuals, race is comprehended as a corporeal substance which can be discovered through scientific analysis. Genetic genealogy thereby promotes a "genetic essentialism" (Arribas-Ayllon 2016;Bliss 2013;Nordgren and Juengst 2009;Roth et al 2020) which renders the individual as biologically bound to a racial group. As Scodari puts it:…”
Section: Gats and Geneticized Identitiesmentioning
confidence: 99%
“…By ascribing racial or ethnic categories to the physical bodies of individuals, race is comprehended as a corporeal substance which can be discovered through scientific analysis. Genetic genealogy thereby promotes a "genetic essentialism" (Arribas-Ayllon 2016;Bliss 2013;Nordgren and Juengst 2009;Roth et al 2020) which renders the individual as biologically bound to a racial group. As Scodari puts it:…”
Section: Gats and Geneticized Identitiesmentioning
confidence: 99%
“…Survey research has shown that GATs prompt people to understand human traits and racial differences as genetically determined (Phelan et al, 2014), even though GATs are often marketed as a means of celebrating diversity and overcoming differences (Bliss, 2013; Bolnick et al, 2007; Lee, 2013). Such claims have led to expectations that individual users of GATs will interpret results as having deterministic implications for their own identities (Bolnick et al, 2007; Nash, 2015; Nordgren and Juengst, 2009).…”
Section: Background and Literaturementioning
confidence: 99%
“…Family norms, sexuality, ethnicity and human-nature relations take centre stage in the political discourse. This involves a coupling of questions of politics, lifestyle and identity to such a degree that lifestyle choices assume a political significance, most explicitly in the quest for environmentally sustainable ways of living (Bliss, 2013;Klandermans, 2014).…”
Section: Introductionmentioning
confidence: 99%